Er-Miao-Fang Extracts Inhibits Adipose Lipolysis and Reduces Hepatic Gluconeogenesis via Suppression of Inflammation - Zhao, Wenjun; Feng, Xin; Liu, Baolin; Xian, Jiechen; Zhang, Ning (Frontiers in Physiology, 2018)
High-fat-diet (HFD) feeding induces adipose dysfunction. This study aims to explore whether the Traditional Chinese Medical prescription Er-Miao-Fang could ameliorate adipose dysfunction and prevent hepatic glucose output. Short-term HFD feeding induced adipose lipolysis accompanied with enhanced hepatic glucose output in mice. Adipose lipolysis is initiated by cAMP/PKA signaling. Oral administration Er-Miao-Fang inhibited inflammation in adipose tissue by dephosphorylation of JNK and reducing TNF-α and IL-1β production, and thus preserved phosphodiesterase 3B (PDE3B) induction, contributing to preventing cAMP accumulation. As a result, from suppression of PKA activation, Er-Miao-Fang reduced fatty acids and glycerol release from adipose tissue due to the inhibition hormone sensitive lipase (HSL). By blocking the traffic of fatty acids and inflammatory mediators from adipose tissue to the liver, Er-Miao-Fang attenuated hepatic cAMP/PKA signaling by protecting phosphodiesterase 4B (PDE4B) induction from inflammatory insult, and thereby reduced hepatic glucose production by suppression of hepatic glucagon response in HFD-fed mice. In conclusion, Er-Miao-Fang prevented adipose lipolysis by suppression of inflammation, contributing to reducing excessive hepatic glucose output. These findings present a new view of regulating gluconeogenesis and provide the guiding significance for the regulation of multi-link targets with Traditional Chinese Medicine.